3D Transient CFD Simulation of Scroll Compressors with the Tip Seal. Issue 1 (July 2015) - Gao, Haiyang; Ding, Hui; Jiang, Yu
Abstract: A new template simulation tool is developed for scroll compressors/expanders capable of modelling tip seal leakages. This scroll template generates a high quality 3D multiblock structured mesh from user-input stationary and orbiting scroll surfaces. The mesh movement is then automatically calculated to account for every position of the orbiting scroll, maintaining good grid quality and smooth movement throughout the whole revolution. A state- of-the-art efficient CFD solver is used to solve Navier-Stokes equations, capable of simulation with both real gas and ideal gas. A case study is presented for a generic scroll compressor with refrigerant R410A. The case was run with and without the tip seal volumes. Comparisons are made to show the impact of tip seals on the compressor performance.